2008
DOI: 10.1007/s00246-008-9303-3
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Echocardiographic Markers and Therapy in Persistent Pulmonary Hypertension of the Newborn

Abstract: Decreased left ventricular size and output correlates with the need for advanced therapies in infants with PPHN. Early identification may allow more effective management and placement of neonates at risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 13 publications
1
33
0
Order By: Relevance
“…Tricuspid regurgitant velocity is used to estimate pulmonary artery pressure, although the precision of the technique is debatable [18]. In previous studies in this population, a tricuspid regurgitant jet has been observed in 70-86% of infants [4,15,16,19]. Other signs of elevated right sided-pressures such as bidirectional or right-to-left shunt across the ductus or atrium have been reported in 73-91% and 73-100% cases respectively [15,16].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Tricuspid regurgitant velocity is used to estimate pulmonary artery pressure, although the precision of the technique is debatable [18]. In previous studies in this population, a tricuspid regurgitant jet has been observed in 70-86% of infants [4,15,16,19]. Other signs of elevated right sided-pressures such as bidirectional or right-to-left shunt across the ductus or atrium have been reported in 73-91% and 73-100% cases respectively [15,16].…”
Section: Discussionmentioning
confidence: 93%
“…Peterson and colleagues evaluated whether conventional ECHO indices on the day of presentation could predict the need for "advanced therapies", such as iNO, ventilation, high frequency oscillation and ECMO [19]. Infants who needed these therapies had lower LVO reflected by a decreased ascending aortic VTI, shorter transverse aortic arch ejection time and absent or retrograde transverse aortic diastolic flow, smaller LV end-diastolic area and right-to-left atrial level shunting [19]. There were no significant correlates with death.…”
Section: Discussionmentioning
confidence: 99%
“…They are, in general, mechanically ventilated, sedated and often paralyzed with muscle relaxants. 20,21 Therefore, procedures such as suctioning, changing endotracheal tubes, bathing and repositioning should be kept to a minimum. Early treatment with surfactant prevents the development of PFC in cases with lung issues.…”
Section: Discussionmentioning
confidence: 99%
“…It help rule out CHD, document right-to-left shunt and estimate PAP from Doppler velocity measurement of tricuspid regurgitation jet [22]. Finally, some cases may require cardiac catheterization to confirm the diagnosis by direct visualization of cardiopulmonary anatomy.…”
Section: Diagnosismentioning
confidence: 99%